Предмет: Математика,
автор: aaaaaaaaaasss
допоможіть будь-ласка з розв*язками!!!
Приложения:
![](https://files.topotvet.com/i/45e/45e92b6c624098972da86da90c367fae.jpg)
Ответы
Автор ответа:
0
4) = 3х²/6 + 2х/4 - 5 = х²/2 + х/2 - 5
5) = 2х(5-х) + (х²+1)(-1) = 10х - 2х² - х² - х = -3х² + 9х
6)=( 2(4х+1)-4(2х+1))/(4х+1)^2 = -2/(4х+1)^2
7) плохо видно, извиняюсь.
5) = 2х(5-х) + (х²+1)(-1) = 10х - 2х² - х² - х = -3х² + 9х
6)=( 2(4х+1)-4(2х+1))/(4х+1)^2 = -2/(4х+1)^2
7) плохо видно, извиняюсь.
Похожие вопросы
Предмет: Английский язык,
автор: 897969
Предмет: Математика,
автор: Аноним
Предмет: Алгебра,
автор: romad18
Предмет: Биология,
автор: mashazya